Computer Laboratory Management in Junior High Schools - Muwafiqus Shobri; Faidatul Bahiyah (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study is to provide an overview of computer laboratory management at UPT SMP Negeri 19 Gresik starting from planning, organizing, implementing, and evaluating computer laboratories, all of which will be explored in this research. The object of research is the head of the laboratory, the head of the school, and teachers. A qualitative descriptive methodology was used for this study. Data were collected by means of in-depth interviews, direct observation, and documentation then followed by data reduction, data presentation, and drawing conclusions. The results of this study indicate that so far UPT SMP Negeri 19 Gresik has been able to manage their computer laboratory effectively, however, there is still potential that needs to be improved, especially in the planning and implementation of computer laboratory management.